GACSON software for automated segmentation and morphology analyses of myelinated axons in 3D electron microscopy. (June 2022) - Behanova, Andrea; Abdollahzadeh, Ali; Belevich, Ilya; Jokitalo, Eija; Sierra, Alejandra; Tohka, Jussi
Highlights: Electron microscopy now allows three-dimensional imaging of hundreds of micrometers of tissue with nanometer-scale resolution. Quantitative analysis of this data requires the instance segmentation of individual ultrastructural components. Here, we present gACSON software for visualization, segmentation, assessment, and morphology analysis of myelinated axons. gACSON segments the intra-axonal space of myelinated axons and their corresponding myelin sheaths. Abstract: Background and Objective: Advances in electron microscopy (EM) now allow three-dimensional (3D) imaging of hundreds of micrometers of tissue with nanometer-scale resolution, providing new opportunities to study the ultrastructure of the brain. In this work, we introduce a freely available Matlab-based gACSON software for visualization, segmentation, assessment, and morphology analysis of myelinated axons in 3D-EM volumes of brain tissue samples. Methods: The software is equipped with a graphical user interface (GUI). It automatically segments the intra-axonal space of myelinated axons and their corresponding myelin sheaths and allows manual segmentation, proofreading, and interactive correction of the segmented components. gACSON analyzes the morphology of myelinated axons, such as axonal diameter, axonal eccentricity, myelin thickness, or g-ratio. Results: We illustrate the use of the software by segmenting and analyzing myelinated axons in six 3D-EM volumes of rat somatosensory cortex after sham surgery or traumatic brain injury (TBI). Our results suggest that the equivalent diameter of myelinated axons in somatosensory cortex was decreased in TBI animals five months after the injury. Conclusion: Our results indicate that gACSON is a valuable tool for visualization, segmentation, assessment, and morphology analysis of myelinated axons in 3D-EM volumes. It is freely available at https://github.com/AndreaBehan/g-ACSON under the MIT license.